Zooming into Eta Carinae with interferometry. Issue Volume 9:Issue S307(2014) (23rd January 2015) - Groh, Jose H.
Abstract: Shaped by strong mass loss, rapid rotation, and/or the presence of a close companion, the circumstellar environment around the most massive stars is complex and anything but spherical. Here we provide a brief overview of the high spatial resolution observations of Eta Carinae performed with the Very Large Telescope Interferometer (VLTI). Special emphasis is given to discuss VLTI/AMBER and VLTI/VINCI observations, which directly resolve spatial scales comparable to those where mass loss originates. Studying scales as small as a few milli-arcseconds allows us to investigate kinematical effects of rotation and binarity in more detail than ever before.